An Artificial Peripheral Neural System Based on Highly Stretchable and Integrated Multifunctional Sensors. (10th April 2021) - Liao, Xinqin; Song, Weitao; Zhang, Xiangyu; Jin, Haoran; Liu, Siyu; Wang, Yongtian; Thean, Aaron Voon‐Yew; Zheng, Yuanjin
Abstract: Prostheses and robots have been affecting all aspects of life. Making them conscious and intelligent like humans is appealing and exciting, while there is a huge contrast between progress and strong demand. An alternative strategy is to develop an artificial peripheral neural system with high‐performance bionic receptors. Here, a novel functional composite material that can serve as a key ingredient to simultaneously construct different artificial exteroceptive sensors (AE sensors) and artificial proprioceptive sensors (AP sensors) is demonstrated. Both AP sensors and AE sensors demonstrate outstandingly high stretchability; up to 200% stretching strain and possess the superior performance of fast response and high stability. An artificial peripheral neural system integrated with the highly stretchable AP sensor and AE sensor is constructed, which makes a significant breakthrough in the perception foundation of efficient proprioception and exteroception for intelligent prostheses and soft robots. Accurate feedback on the activities of body parts, music control, game manipulation, and wireless typing manifest the enormous superiority of the spatiotemporal resolution function of the artificial peripheral neural system, all of which powerfully contribute to promoting intelligent prostheses and soft robots into sophistication, and are expected to make lives more fascinating. Abstract : Two different types of artificial bionic sensors are simultaneously constructed by the same functional composite through ingenious structural design for an artificial peripheral neural system. The artificial bionic sensors feature unprecedented high stretchability and exhibit superior performance. The artificial peripheral neural system performs extremely well.